The Urgency of Implementation Top And Down Principles Towards Red And White Cooperatives In Indonesia - Ulfanora, Ulfanora (Faculty of Law, Andalas University, 2025)
After the election of Mr. Prabowo Subianto, he has launched breakthroughs aimed at changing Indonesia for the better in the future. One of the breakthroughs that Mr. Prabowo Subianto has made includes Danantara as Indonesia's SWF, Free Nutritious Meals (MGB), and the Red and White Cooperative. In these three projects, the author will examine the existence of the Red and White Cooperative which has been ratified through Presidential Instruction Number 9 of 2025 concerning the Acceleration of the Establishment of Red and White Village/District Cooperatives. With Presidential Instruction Number 9 of 2025, all cooperatives that have been established in villages will be replaced with the Red and White Cooperative. This change actually goes against the founding values of cooperatives, namely deliberation and democracy. This research is legal research with a statutory approach, analytical approach and conceptual approach. The results of this research explain that firstly, the application of the nature of investment capital in cooperatives certainly cannot be applied absolutely to the risks that occur but is only limited to business risks that occur in the business sector financed by investors. Second, in Indonesia, even though the concept of cooperatives is covered by law, the existence of cooperatives still cannot run effectively. Third, on the economic side, the urgency of establishing the Red and White Cooperative is a good breakthrough for fulfilling the economic welfare of village communities. But from a legal perspective, it is necessary to understand the Top & Down principle in formation so that the capital carried out by the central government does not fulfill the principles of forming cooperatives based on kinship, democracy and independence. Then, in Law Number 6 of 2014 concerning villages, villages are actually the subject of development, so the formation of cooperatives should be based on the decisions of the village community.